Development Reading and Writing Ability of Grade 4 Students by Learning Management Based on Picture Word Inductive Model. - Janatkon, Kanokporn; Chano, Jiraporn (Journal of Education Rajabhat Maha Sarakham University, 2022)
The research objectives were to improve reading and writing ability of grade 4 students according to 70% criteria. The target group was 3 out of 8 students in grade 4 of Bannongkun school, Keadam district, Mahasarakham province, Mahasarakham primary education service area office 1. There were three research tools included 1) The Thai language learning plans based on Pictures Word Inductive Model, PWIM in the topic of “ Could be read and write with the spelling section” for 4 units which were 4 hours each, for a total of 16 hours The mean suitability of the learning plan was 4.77, 2) The reading test is divided into 2 parts. Part 1 is a 20-item 4 choice test. Part 2 is a vocabulary reading test. There are evaluation criteria. Literally correct reading readability and reading at the specified time of 10 items with IOC values ​​between 0.60-1.00 and 3) writing test There are scoring criteria in the assessment. naming The essence of the subject, the use of language, writing and spelling orderliness and correct according to the explanation number 1 item with IOC value between 0.60-1.00 The data analysis statistics were percent, mean and standard deviation. The results were found that 1) Students could read the spelling section that was Mae Kok, Mae Kud, Mae Kub and Mae Kon for 71 percent which met the required criteria of 70 percent. 2) Students could write the spelling section that was Mae Kok, Mae Kud, Mae Kub and Mae Kon for 70.5 percent which met the required criteria of 70 percent.